1994
DOI: 10.1093/geronj/49.5.s231
|View full text |Cite
|
Sign up to set email alerts
|

Women's Labor Force Participation in Later Life: The Effects of Early Work and Family Experiences

Abstract: The purpose of this study was to develop and evaluate a model of labor force participation among a group of older women in the United States. A comprehensive measure of women's combined work and family experiences across the adult life course was created. Employing data from the 1984 Survey of Income and Program Participation, we applied multinomial logistic regression techniques to examine the association between work-family experiences and later life labor supply. Our findings generally support an attachment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
83
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 0 publications
3
83
2
Order By: Relevance
“…Even though insights are still rather fragmented -given that studied earlier life experiences and country contexts differ much between studies -a general sketch of some findings could be provided. With respect to labor force participation, research findings have shown that women who have worked continuously throughout the life course are more likely to work during later life (Pienta et al 1994), and to work beyond pension age (Finch 2014), which seems to be in line with the notion of continuity between earlier and later points in time in terms of labor participation. For men, the findings are mixed, with some studies showing that a history of unemployment and labor force exits places male workers at a higher risk of retirement (Hayward et al 1998), and other studies showing that discontinuous employment and involuntary job loss in mid-life result in lower odds of retirement , Raymo et al 2011.…”
Section: Work Histories and Retirement Timingmentioning
confidence: 53%
See 2 more Smart Citations
“…Even though insights are still rather fragmented -given that studied earlier life experiences and country contexts differ much between studies -a general sketch of some findings could be provided. With respect to labor force participation, research findings have shown that women who have worked continuously throughout the life course are more likely to work during later life (Pienta et al 1994), and to work beyond pension age (Finch 2014), which seems to be in line with the notion of continuity between earlier and later points in time in terms of labor participation. For men, the findings are mixed, with some studies showing that a history of unemployment and labor force exits places male workers at a higher risk of retirement (Hayward et al 1998), and other studies showing that discontinuous employment and involuntary job loss in mid-life result in lower odds of retirement , Raymo et al 2011.…”
Section: Work Histories and Retirement Timingmentioning
confidence: 53%
“…With respect to work careers these studies have, for instance, investigated the role of diverse career pathways (Han and Moen 1999, Pienta et al 1994, Kovalenko and Mortelmans 2013, exposure to certain types of jobs over the career (Elder and Pavalko 1993, Hayward et al 1998, Raymo et al 2011, and diverse indicators of employment continuity and career mobility (Damman et al 2011, Finch 2014, Raymo et al 2010, Singh and Verma 2003, Henretta et al 1993) for explaining late-career labor market behaviors. Even though insights are still rather fragmented -given that studied earlier life experiences and country contexts differ much between studies -a general sketch of some findings could be provided.…”
Section: Work Histories and Retirement Timingmentioning
confidence: 99%
See 1 more Smart Citation
“…While a few qualitative studies have discussed retirement in light of earlier experiences in different life spheres (August & Quintero, 2001;Higgs, Mein, Ferrie, Hyde, & Nazroo, 2003), quantitative studies have principally focused on the impact of earlier life experiences in one life sphere − the work sphere − on one aspect of the retirement process, namely retirement behavior (Elder & Pavalko, 1993;Hayward, Friedman, & Chen, 1998;Mutchler, Burr, Pienta, & Massagli, 1997;Raymo, Warren, Sweeney, Hauser, & Ho, 2009;Singh & Verma, 2003). A small number of quantitative studies has investigated the impact of earlier life experiences in both work and family life spheres on retirement (e.g., Szinovacz & DeViney, 1999, but these studies have mainly focused on women (Hank, 2004;O'Rand & Henretta, 1982;Pienta, 1999;Pienta, Burr, & Mutchler, 1994). Besides, only a few studies have paid attention to the relationships between midlife experiences and aspects of the retirement process that precede retirement behavior (Han & Moen, 1999;Raymo, Warren, Sweeney, Hauser, & Ho, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The limited evidence collected so far tends to suggest that having children might actually delay women's exit from the work force (Hank, 2004). These and related findings have been interpreted as reflections of gendered role patterns developed across the family life course (Henretta et al, 1993;Pienta et al, 1994), but they are also likely to be affected by welfare state policies and institutions -which are not gender neutral either (Daly & Rake, 2003).…”
mentioning
confidence: 99%